THE DIFFERENCE QUALITY OF LIFE LEVEL IN ELDERLY WOMEN AT THE COMMUNITY AND THE AGING INSTITUTION - Setyoadi, Setyoadi; Noerhamdani, Noerhamdani; Ermawati, Fela (Jurnal Keperawatan, 2011)
The progress of science and technology and improvement of socio-economic impact on improving community health status and life expectancy, so the number of elderly population is also increasing. The number and life expectancy in elderly women is higher, it has a lower quality of life than elderly men. Efforts to improve the quality of life of elderly in Indonesia through community service and nursing. Both these services have different settings and facilities that affect the quality of life ofelderly. The aim is to know the difference in quality of life in elderly women in the community and in nursing, in terms of physical health, psychological, social relationships, and environment. Comparative research design with descriptive analytic cross sectional approach. The sample of 44 respondents to the research community and the 36 respondents to the nursing group are taken by wayof purposive sampling. Mann whitney test results, with ? = 0,05 concluded there was no difference in the level of quality of life in elderly women in the community and nursing (p = 0,477). Based on the results of research can be encouraged to continue improving the environmental aspects of women's increased productivity, access to health services and information in elderly women, particularly in elderly women in nursing.